Possible mechanisms of spermatogenic dysfunction induced by viral infections: Insights from COVID‐19 - Keisuke Okada; Chanhyon Kin; Yosuke Yamashita; Shun Kawamura; Katsuya Sato; Koji Chiba; Hideaki Miyake (Reproductive Medicine and Biology)
Abstract Background As the COVID‐19 pandemic nears resolution in 2024, the mechanisms by which SARS‐CoV‐2 and other viral infections induce spermatogenic dysfunction remain poorly understood. This review examines the mechanisms by which viral infections, particularly COVID‐19, disrupt spermatogenesis and highlights the implications for male reproductive health. While reports suggest that spermatogenic dysfunction caused by COVID‐19 is mild and transient, these findings may have broader applications in understanding and treating spermatogenic dysfunction caused by future viral infections. Methods The PubMed database was searched to identify original and review articles investigating the mechanisms by which viral infections, particularly SARS‐CoV‐2, contribute to spermatogenic dysfunction. Main Findings SARS‐CoV‐2 affects the testis through multiple mechanisms, including ACE2 receptor‐mediated entry, direct viral damage, inflammatory response, blood–testis barrier disruption, hormonal imbalance, oxidative stress, and impaired spermatogenesis. The combination of these factors can disrupt testicular function and highlights the complexity of the effects of COVID‐19 on male reproductive health. Conclusion COVID‐19 may disrupt spermatogenesis through direct testicular infection, systemic inflammation, hormonal disruption, and oxidative stress. Ongoing research, vaccination efforts, and clinical vigilance are essential to address these challenges and develop effective treatment and prevention strategies.